GEOGRAPHICAL ASPECTS OF THE DEVELOPMENT OF FREE ECONOMIC ZONES IN UZBEKISTAN - Umarova Khurshida (Журнал естественных наук, 2022)
The article analyzes the free economic zones established in the Republic of Uzbekistan and their territorial location, as well as their role in the country’s economy. The world experience of the development of free economic zones has been studied, and attention has been paid to the need to increase them on the basis of existing regional economic opportunities.